Incorporating rainwater harvesting systems into the design of green infrastructure, alongside constructed wetlands and fishponds - Taufikurahman, Taufik; Susila, Endra; Ginanjar, Tetep; Rizkyani, R. R. Deby Anindya (Universitas Mercu Buana, 2024)
In rural areas grappling with recurring water scarcity during dry periods, the imperative for water conservation becomes evident. This research centers on Green Infrastructure (GI), showcasing its substantial potential for better water management practices, specifically in the realms of rainwater harvesting and greywater treatment. We implemented an integrated household-scale rainwater harvesting system (RWH) coupled with greywater processing using a constructed wetland (CW). The constructed wetland, filled with sands and gravels and adorned with Napier grass (Pennisetum purpureum), served as a filtration medium for both greywater and rainwater before channelling them into a fishpond. The project was conducted at the ITB research station in Haurngombong village, Pamulihan sub-district, Sumedang, West Java. The project exemplified an effective synergy between the RWH system and a constructed wetland for greywater treatment, benefiting both plant irrigation and fishpond utilization. The demonstrated approach holds significant potential added value for communities, serving as a reservoir for crop irrigation, supporting fish farming, and facilitating greywater treatment through an integrated aquaponic system.